Jesus [videorecording (DVD)] - Sisto, Jeremy, 1974-; Bisset, Jacqueline, 1944-; Messing, Debra, 1968-; Mueller-Stahl, Armin, 1930-; Oldman, Gary; Couture, Suzette (Bible collection., 2020)
Looks at the life of Jesus from His humble beginnings as a carpenter through His extraordinary life and the mission of His spiritual destiny.